Convergence Analysis of the Sanitation Index for 158 Countries - Chang, YuSang; Lee, Yoo-Taek; Lee, Yoonji; Jin, MyungHoon (Journal of Environmental Accounting and Management, 2026)
Since 1990, 2.1 billion people in the world gainedaccess to improved sanitation by 2015. However, 2.4 billion people still did not use a basic toilet. We examined whether the country differences in the sanitation index existing in 1990 had narrowed. We deployed convergence methodology to answer the questions for 158 countries. Results of our analysis indicate that the sanitation indexes for 158 countries were converging toward a rapid reduction of dispersion and a moderate catch-up. The speed of dispersion reduction was led by the upper middle income group, together with the South Asia region. The speed of catch-up was led by the low income group and the East Asia Paciﬁc region. The policy implication from this study is that individual countries should be guided by the speeds of catch-up and dispersion reduction estimated from the appropriate subgroup where they belong for evaluating their future progress.